The relationship between labor migration and entrepreneurship during the recovery of national economies after the COVID-19 pandemic - Veronica Margarita Trillo-Espinoza; Galina Volkovitckaia; Sergei Chernov (Journal of Innovation and Entrepreneurship)
Abstract Against the backdrop of the challenges posed by the COVID-19 pandemic, investigating the relationship between labor migration and entrepreneurship becomes particularly relevant, as it unveils the potential utilization of migration flows as a stimulus for economic recovery and growth. The aim of the study was to establish the correlation between labor migration and entrepreneurship during the recovery of national economies post-COVID-19 pandemic. To achieve this objective, statistical data from official sources and a structured online survey (544 respondents—labor migrants from post-Soviet countries) were utilized. Processing and interpretation of the results involved a range of econometric methods and correlation analysis. The study revealed a significant correlation between labor migration and the number of new enterprises in the post-Soviet economic space. It was found that migrant wages are often lower than those of host country citizens for similar work. Additionally, employers in the host country are mainly interested in obtaining cheap labor. However, almost all respondents aim to maximize wage values and rarely consider the possibility of starting a business in the host country as a viable alternative to wage labor. Survey results indicated that the new experience in the host country positively influences entrepreneurial potential, and additional financial resources increase opportunities for business development in the country of origin. Therefore, the study results provided empirical evidence for previously formulated hypotheses and suggested possible avenues for promoting entrepreneurship in both host and origin countries of migrants. The result of this research was the empirical confirmation of all the hypotheses. The results presented in this paper are intended for practitioners in the field of public and municipal administration, as well as for academic researchers, as they may be utilized for policy decision-making or the implementation of relevant measures, particularly in support of labor migrants. The findings allow for the formation of promising areas for further research.